The Receptors that Mediate the Direct Lethality of Anthrax Toxin - Liu, Shihui (MDPI, 2012)
Tumor endothelium marker-8 (TEM8) and capillary morphogenesis protein-2 (CMG2) are the two well-characterized anthrax toxin receptors, each containing a von Willebrand factor A (vWA) domain responsible for anthrax protective antigen (PA) binding. Recently, a cell-based analysis was used to implicate another vWA domain-containing protein, integrin β1 as a third anthrax toxin receptor. To explore whether proteins other than TEM8 and CMG2 function as anthrax toxin receptors in vivo, we challenged mice lacking TEM8 and/or CMG2. Specifically, we used as an effector protein the fusion protein FP59, a fusion between the PA-binding domain of anthrax lethal factor (LF) and the catalytic domain of Pseudomonas aeruginosa exotoxin A. FP59 is at least 50-fold more potent than LF in the presence of PA, with 2 μg PA + 2 μg FP59 being sufficient to kill a mouse. While TEM8(−/−) and wild type control mice succumbed to a 5 μg PA + 5 μg FP59 challenge, CMG2(−/−) mice were completely resistant to this dose, confirming that CMG2 is the major anthrax toxin receptor in vivo. To detect whether any toxic effects are mediated by TEM8 or other putative receptors such as integrin β1, CMG2(−/−)/TEM8(−/−) mice were challenged with as many as five doses of 50 μg PA + 50 μg FP59. Strikingly, the CMG2(−/−)/TEM8(−/−) mice were completely resistant to the 5-dose challenge. These results strongly suggest that TEM8 is the only minor anthrax toxin receptor mediating direct lethality in vivo and that other proteins implicated as receptors do not play this role.